Comportamiento agronómico e incidencia a plagas de tres híbridos de maíz (Zea mays.) En la zona de Babahoyo - Espín Mancilla, Roddy José (2020)
The present investigation was carried out on the grounds of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7.5 via Montalvo. Three corn hybrids and two planting distances were investigated in three repetitions. The objective of the work was to evaluate the agronomic behavior and incidence to plagues of the hybrids raised in this zone of the Ecuadorian Coast. Corn planting was done with Dekalb 7088, Emblem 777 and Bm 905 materials in experimental units of 30 m2. The treatments were distributed in a split plot design. The evaluation of means was performed with the Tukey significance test at 5%. The variables evaluated were: plant height, insertion height, days of flowering, days of harvest, stem diameter, diameter of ears, length of ears, grain weight, yield per hectare, incidence of pests and economic analysis. The results show that the highest grain yield was obtained in the hybrid Dekalb 7088 planted at 71428 plants / ha) with 8134,17 kg / ha. In addition, the same material showed the greatest net profit and profit. The hybrid Dekalb 7088 was the one with the lowest incidence of Spodoptera frugiperda and Diatrea saccharalis with 28,36% and 9,13% respectively.